Critical care nurses’ knowledge regarding prevention of central venous catheter-related infection in Saudi Arabia: A cross-sectional study - Alshammari, Bassam Shyhan; Alsaqri, Salman Hamdan; Alkubati, Sameer A.; Llego, Jordan H.; Al-Sadi, Ahmad K.; Ali, Aziza Z.; Elsayed, Wessam A.; Balawi, Anas Mahmoud; Nageeb, Shaimaa Mohamed; Hamed, Laila A. (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Central venous catheter-related infections (CVC-RIs) are a significant concern in intensive care units (ICUs), contributing to increased morbidity, mortality, and healthcare costs. Nurses play a crucial role in preventing these infections through proper catheter care, adherence to aseptic techniques, and early detection of complications. However, knowledge gaps may hinder effective infection prevention and patient outcomes. Objective: This study aimed to evaluate ICU nurses’ knowledge of CVC-RI prevention and identify factors influencing their knowledge. Methods: A cross-sectional study was conducted among 202 ICU nurses in Al-Jouf, Saudi Arabia, from April to June 2023. Data were collected using a self-reported questionnaire assessing knowledge across eight domains: CVC-RI pathophysiology, diagnosis, catheter insertion sites, frequency of CVC changes, skin antisepsis, dressing changes, use of antibiotics/antiseptic ointments, and general CVC care. Statistical analyses included frequency, percentage, mean, standard deviation, Mann-Whitney, Kruskal-Wallis, and univariate and multivariate logistic regression. Results: The mean knowledge score was 5.8 ± 2.3. The highest knowledge was observed in catheter insertion sites (47.8% of the total score), followed by CVC-RI diagnosis (34.9%) and dressing change frequency (40.3%). The lowest score was in CVC-RI pathophysiology (14.6%), indicating a significant knowledge gap. Age, education, training on CVC-RI prevention, and the source of information significantly influenced knowledge (p <0.05). Multivariate analysis revealed that education (p = 0.002) and receiving information on CVC-RI (p = 0.007) were significant predictors of higher knowledge. Nurses who received information from the Infection Control Unit demonstrated the highest knowledge levels (p = 0.008). Conclusion: The findings emphasize the need for targeted educational programs and continuous professional development to address knowledge gaps in CVC-RI prevention. Healthcare institutions should prioritize up-to-date curricula, ongoing training initiatives, and reliable information sources to enhance ICU nurses’ ability to prevent catheter-related infections and improve patient care outcomes. It is essential for nurses to actively engage in ongoing training to close knowledge gaps and enhance their role in infection prevention.